ANALYZING MARKET TRENDS IN THE AUTOMATION ERA FOR THE DEVELOPMENT OF INDEPENDENT CAMPUS CURRICULUM - Sya'baningrum Prihhartini; Endang S. Priyatna (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2022)
This research focuses on reading market trends for curriculum development conducted through library research. The development of automation technology, including artificial intelligence (AI), robots, and algorithms, has made the workforce undergo massive changes concerning workers and jobs. It is estimated that by 2030, 23 million jobs will be automated, 27 to 46 million new jobs will be created, and 10 million of these will be new types of work. The Ministry of Education and Culture of Indoensia has responded to the changes with the launch of the Kurikulum Kampus Merdeka (Freedom to learn curriculum), which aims to equip the graduates with industry-needed employability skills. In order to achieve this goal, higher educations need to know the job prospects and skills relevant to the workplace, so that the mismatch between what graduates learn in college and the skills demanded by the employers can be minimized.